The Planetary Wave Activity in Temperatures of the Stratosphere, Mesosphere and in Critical Frequencies of Ionospheric F2 Layer - N. M. Polekh; G. V. Vergasova; E. S. Kazimirovsky; N. P. Perevalova; V. I. Kurkin; M. A. Chernigovskaya (International Journal of Geophysics)
A large body of experimental evidence lends credit to the existence of a close relationship between ionospheric parameters and the underlying atmosphere. Vertical-incidence ionospheric sounding data and temperature measurements at stratospheric (30 km) and mesospheric (80 km) heights have been used in investigating the interrelation between the occurrence of fluctuations with periods of planetary waves in temperature variations at different heights and in F2 layer critical frequency variations (foF2) under low solar activity conditions for the time interval 2006-2007. The distinctive characteristics of the manifestation of common periodicities of the wave structures under consideration are discussed. The statistically significant periods of stratospheric and mesospheric temperature fluctuations vary from 11 to 49 days, whereas foF2 periodograms show higher-frequency fluctuations with periods of 5, 8, 9, and 10 days. The study revealed a similarity between periodic structures for the variations in the parameters involved.